PCLN-03. ORTHOTOPIC TRANSPLANTATION OF PAEDIATRIC GLIOMA STEM CELLS IN MICE MIRRORS THE CLINICAL COURSE OF THE PATIENT. Issue 2 (22nd June 2018) - Wenger, Anna; Larsson, Susanna; Dósa, Sándor; Sabel, Magnus; Kling, Teresia; Carén, Helena
Abstract: BACKGROUND: The leading cause of cancer-related mortality among children is brain tumours and glioblastoma multiforme (GBM) has the worst prognosis. Epigenetic deregulation is believed to be a driver as these patients have few mutations compared to adults. New treatments are urgently needed but few pre-clinical in vivo models exist. One approach of generating these is to transplant tumour tissue into mice, but it yields highly variable results and requires serial passaging in mice, which is time-consuming, expensive and ethically questionable. We therefore aimed to establish a cell line-based orthotopic mouse model representative of the patient tumour. METHODS: Patient-derived cancer stem cell (CSC) lines from paediatric GBM were orthotopically transplanted into immunodeficient mice. The xenograft tumours were evaluated by histology for glioma features. Genome-wide DNA methylation analysis was performed on the CSC, xenograft and patient tumours. RESULTS: All CSC lines initiated tumours and the survival of the mice correlated with the survival of their respective patient. The xenograft tumours had key glioma features and were classified as GBM by histology and methylation profiling. The methylation profile of the xenograft tumour clustered together with the patient tumour (<3% of CpG sites changed methylation status) and the injected CSC line. CONCLUSIONS: We have established a robust and reproducible xenograft model for GBM based on primary CSC lines. The xenograft tumours accurately reflected the patient tumours and mirrored the clinical course of the patient. This model is therefore ideal for accurately predicting patient response from pre-clinical studies of new treatment schedules.